De la finance au travail. Sur les traces des dispositifs de financiarisation - Isabelle Chambost (La Nouvelle Revue du Travail)
The diffuse and complex phenomenon of financialization is difficult to grasp. This research attempts to trace the financialization manufactures devices at work, trying to isolate the impacts of financialization in themselves and to show their continuity from a macroeconomic context to a micro level, from the structure of the finance industry and how it can configure companies and mark labor in its various dimensions. For this purpose it relies on the study of the private equity financial industry, known for its financial arrangements with leverage (LBO), because of its symbolic nature and circumstances that give rise to rupture, during the acquisition of firms. This research uses a series of semi-structured interviews conducted with unionists, work-councils representatives and managers of private equity funds.